Functional System Safety - Simulator Environment - Gustavsson, Petter; Roslund, Henrik (My University, 2010)
In recent years strictly mechanical solutions have evolved towards electromechanical which have introduced an increase in complexity that cannot be ignored. This is especially important for safety critical systems and the way they are developed. This thesis is part of a project with the goal of evaluating the development process ISO26262 concerning safety critical systems in vehicles. The result of this thesis is a multi-interfaced presentation system for demonstrating the effects of not correctly handling hazards in a Steer-by-Wire system. The presentation system is written in C/C++ programming languages and connects different interfaces such as; Vehicle Simulator, CAN communication, HUD presentation, Microcontroller and Steering controls.
Keywords: Programvaruteknik; Software Engineering